(3OjhGf GdUaOjs - (3GdUaOj, GdCdnHpcj, CHh GdUaGA, UdGM GdOjf, Ndjd Hf CjHc Hf YHO Gddg, J (B764(3g`s
(3ChdgG (B:s
(3bVi hgPG GdPj aj MHge jMH (B*** (3aj PeI GdhLO Jdc GdQhMs
(3BNQgG (B:s
(3YedJg HGH GdeVGa JaGDdG (B*** (3hQbjHg jZQjg HGdJfhjfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 2 / 315s
(3eYLe GdeDdajf(B: 1 / 680s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdCOHs